Emerging issues in Catholic bioethics - Eberl, Jason T. (Philosophy and medicine, 2026)
Like its predecessor, Contemporary Controversies in Catholic Bioethics, this volume gathers together an array of Catholic scholars with expertise in theology, philosophy, medicine, ethics, health administration, and pastoral care. Expanding the range of bioethical issues from the previous volume, the topics treated within this volume include transgender identity, disability, public and global health, and artificial intelligence, as well as specific controversies that arose during the COVID-19 pandemic concerning the allocation of scarce life-sustaining resources and vaccination policies. Drawing upon the Catholic Church s intellectual tradition and more recent bioethical teachings, two chapters address each topic representing diverse, sometimes divergent, perspectives. This volume will be a valuable resource for scholars in bioethics or Catholic studies, who will benefit from the nuanced arguments offered based on the latest research. This volume will also be instructive for students entering the field to become aware of the founding philosophical and theological principles informing the Catholic bioethical worldview